Russian League Against Epilepcy: the answer to the present challenge - V. A. Karlov (Эпилепсия и пароксизмальные состояния)
Closing the conference, Professor V.A. Karlov, President of the Russian League Against Epilepsy (RLAE), shows how to use it’s potential to solve the most important tasks set for the present domestic medicine. He touches upon the problems of health care financing, treatment of epilepsy “through life”, interdisciplinary interaction of epileptologists with obstetricians and gynecologists, neurologists, psychiatrists, neurosurgeons, as well as the state of the epileptological service in the Russian Federation as a whole.